Local control and failure patterns after intensity modulated radiotherapy with reduced target volume delineation after induction chemotherapy for patients with T4 nasopharyngeal carcinoma - Fang-Fang Kong; Meng-Shan Ni; Rui-Ping Zhai; Hong-Mei Ying; Chao-Su Hu (Translational Oncology, 2022)
Background: The delineation of target volume after induction chemotherapy(IC) for nasopharyngeal carcinoma(NPC) is currently controversial. In this study, we aimed to analyze the long-term local control(LC) and failure patterns of T4 NPC treated with reduced target volume radiotherapy after IC. Methods: From September 2007 to January 2013, 145 patients with T4 NPC were retrospectively reviewed. All patients received at least 1 cycle of IC followed by intensity modulated radiotherapy(IMRT). The gross tumor volume(GTV) was delineated according to the post-IC images for intracavity tumors and lymph nodes. The LC and overall survival (OS) rates were calculated using the Kaplan-Meier method. The location and extent of local failures were transferred to the pretreatment planning computed tomography (CT) for dosimetric analysis. Results: With a median follow-up time of 95 months (range, 16–142 months), 23 local failures were found. The estimated 10-year LC and OS rates were 81.1%and 54.8% respectively. Among the 20 local failures with available diagnostic images, 18(90%) occurred within the 95% isodose lines and were considered in-field failures and 2(10%) were marginal. There was no outside-field failure. Conclusions: In-field failure was the major pattern of local failure for T4 NPC. IMRT with reduced target volume after IC seems to be feasible. Further researches exploring optimal volume and radiation dose for local advanced NPC in the era of IC are warranted.